REGENERASI KETERLIBATAN ANAK USIA SEKOLAH DALAM PENYALAHGUNAAN MIRAS DI DUSUN TIBU AMBUNG DESA LEMBAH SARI KECAMATAN BATU LAYAR - Riadi Riadi; Muhammad Isnaeni (Universitas Islam Negeri (UIN) Mataram, 2016)
This study aims to describe the problem relating to school children and adult (around 7 to 21 years old) engagement in alcoholic drink. The research is a descriptive analysis which has been conducted around five months in Batu Layar District, West Lombok, West Nusa Tenggara. It is found that the factors caused their engagement in alcoholic drink are: their low level of education, economic weaknesses, lack of parent control, and environment that support them to close to alcoholic drink.